ON THE USE OF NAMES OF MELON AND GOURD CROPS IN THE KHOREZM REGION (International journal of artificial intelligence, 2025)
This article analyzes the names of melon (qovun) and gourd (qovoq) seed varieties cultivated in the Khorezm region. The study focuses on the linguistic and cultural features of these names, their etymology, and their reflection of the region’s agricultural traditions. The research also explores the influence of neighboring Turkic languages on the formation of these plant names and their role in everyday speech and folk terminology.